NILAI DAN FILOSOFI TRADISI SEDEKAH DESO PADA MASYARAKAT DUSUN GEDIPAN KABUPATEN TEMANGGUNG - Kurniyawan, Handi; Rahmat, Rahmat (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2023)
Sedekah deso is one of the traditions that has always existed and is still performed by the people of Gedipan Village, Temanggung Regency amid the progress and development of science and technology. In its implementation, there are philosophical meanings and character values contained in the tradition. Therefore, the purpose of this study is to explain and explore the philosophical meanings and character values contained in the sedekah deso tradition. The research design that used in this research is a qualitative research approach with a descriptive research type. The data collection techniques that used in this study were interviews, observations, and documentation. The results of this research indicate that the sedekah deso tradition performed by the people of Gedipan Village has the meaning of community gratitude to God Almighty as well as a form of sharing with others for the sustenance they have received for a year. Its tradition also has several character values. These character values are communication, discipline, unity, religion, social care, and tolerance. These character values are very relevant to the values contained in Pancasila. Therefore, the researcher hopes that such traditions will continue to be preserved so as not to be lost in modernization and globalization